Modified fenestrated/branched endovascular aortic repair with short bridging stent to treat complex aortic dissection - Zhao, Zihe; Han, Yuexue; Keyoumu, Reyaguli; Zhang, Shuai; Gao, Xia; Liu, Zhao (Frontiers in Cardiovascular Medicine, 2024)
ObjectivesThis study aims to improve fenestrated/branched endovascular aortic repair (F/B EVAR) through fabricating physician-modified stent grafts (PMSG) with short bridging stent to treat complex aortic dissection.MethodsFrom November 2018 to January 2024, a total of 82 aortic dissection patients were treated by F/B EVAR combined with short bridging stents, including 19 aortic arch dissection patients and 63 thoracoabdominal aortic dissection patients. Inner or outer short bridging stents were applied to fabricate PMSG with the help of 3D-printing models intraoperatively. All patients underwent postoperative evaluation by enhanced computed tomography in follow-up.ResultsAll aortic dissections were successfully repaired. In aortic arch group, the average operative time was 289.2 ± 88.8 min. The perioperative mortality rate was 5.3%. The total reintervention rate was 5.3%. The average follow-up duration of 36.2 ± 9.5 months. The total incidence of endoleak after surgery was 15.8%. In thoracoabdominal aorta group, the average operative time was 345.5 ± 112.0 min. The perioperative mortality rate was 1.6%. The total reintervention rate was 1.6%. The average follow-up duration of 32.4 ± 19.2 months. The total incidence of endoleak after surgery was 11.1%.DiscussionThe application of short bridging stents has shown promising results in reducing endoleak rates after F/B EVAR. 3D-printing is a feasible way to assist the precise fenestration and design of short bridging stents. However, the safety and reliability of this method need to be further validated.